2013
DOI: 10.3109/08820139.2013.809580
|View full text |Cite
|
Sign up to set email alerts
|

IL4 and IFNalpha generation of dendritic cells reveals great migratory potential and NFkB and cJun expression in IL4DCs

Abstract: Dendritic cells (DCs) recently revealed as a potent tumor vaccine component, are commonly differentiated from monocytes by cultivation with IL-4 and GM-CSF. Despite the different opinions, the use of IFNalpha can promote DCs differentiation and activation. The aim of this study was to compare the functionality and phenotypic characterization of monocyte-derived DC generated by IL-4 (IL4DC) and IFNalpha (IFNalphaDC) modified protocols. To this aim, we investigated the expression of maturation markers, co-stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…An initial study showed that miR-146 expression was lower in dendritic cells originated from monocytes grown in the presence of IL-4 and GM-CSF, compared to dendritic cells originated by cultivation of monocytes in the presence of IFN-α [ 18 ]. The lower miR-146 expression in these cells is accompanied by an increased migratory capacity and NF-ĸB expression [ 19 ]. miR-146a and particularly miR-146b expression were markedly up-modulated during maturation of monocytes to dendritic cells using GM-CSF and IL-4: particularly, miR-146a and miR-146b expression was about 10–40-fold, respectively, higher than in monocytes [ 20 ].…”
Section: Mir-146 Mir-155 and Innate Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…An initial study showed that miR-146 expression was lower in dendritic cells originated from monocytes grown in the presence of IL-4 and GM-CSF, compared to dendritic cells originated by cultivation of monocytes in the presence of IFN-α [ 18 ]. The lower miR-146 expression in these cells is accompanied by an increased migratory capacity and NF-ĸB expression [ 19 ]. miR-146a and particularly miR-146b expression were markedly up-modulated during maturation of monocytes to dendritic cells using GM-CSF and IL-4: particularly, miR-146a and miR-146b expression was about 10–40-fold, respectively, higher than in monocytes [ 20 ].…”
Section: Mir-146 Mir-155 and Innate Immunitymentioning
confidence: 99%
“…pDCs constitutively express miR-146a levels much higher than mature monocytes: however, miR-146a expression is strongly activated in monocytic cells, but not in pDCs by IFN-γ, IL-1β and lipopolysaccharide (LPS) [ 22 ]. miR-146a expression is up-modulated during differentiation of pDCs by the transcription factor PU.1, and by itself, miR-146a was unable to affect DC differentiation [ 19 ]. miR-146a expression in pDCs is markedly up-modulated upon activation of primary pDCs using TLR7 or TLR9 agonists [ 23 ].…”
Section: Mir-146 Mir-155 and Innate Immunitymentioning
confidence: 99%
“…Accordingly, the LPS-induced increases in expression of IL-12p70 protein in, migration of and ROS production in VitE-treated DCs were significantly reduced, all effects were virtually abolished after suppressing klotho synthesis with klotho siRNA. Moreover, the effects are modulated through NF-κB activation [15, 31]. Therefore, this signaling could participate in regulation of klotho expression.…”
Section: Discussionmentioning
confidence: 99%
“…The development and enhancement of these cell culture techniques led to increasing cell yields throughout the 1990s, which allowed the exploration of the pulse of DCs with tumor antigens as a new potential anticancer vaccines [59,60]. The most commonly used conventional protocols employ peripheral blood mononuclear leukocytes that are differentiated ex vivo into monocytes and later on into mature dendritic cells [61,62], which are then pulsed with specific tumor antigens in various forms, such as synthetic peptides [63], tumor nucleic acid [64], and apoptotic bodies [65] among others.…”
Section: Tumor-derived Exosomes (Tex)mentioning
confidence: 99%